Dependability and Treatment Sensitivity of Multi-Item Direct Behavior Rating Scales for Interpersonal Peer Conflict. (December 2017) - Daniels, Brian; Volpe, Robert J.; Briesch, Amy M.; Gadow, Kenneth D.
Direct behavior rating (DBR) represents a feasible method for monitoring student behavior in the classroom; however, limited work to date has focused on the use of multi-item scales. The purposes of the study were to examine the (a) dependability of data obtained from a multi-item DBR designed to assess peer conflict and (b) treatment sensitivity of Direct Behavior Rating Multi-Item Scales (DBR-MIS) constructed using factor-derived and individualized methods. Analyses were performed using teacher ratings of 65 students (53 boys, 12 girls) between 6 and 12 years old. Results of decision studies indicated that an acceptable criterion of dependability (ϕ > .70) for low-stakes, intraindividual decision making could be achieved using a three-item scale across eight occasions, a four- or five-item scale across four occasions, or a six-item scale across three occasions. Subsequent analyses verified that a six-item DBR demonstrated acceptable treatment sensitivity when ratings were conducted on 3 days during baseline and 3 days during treatment with methylphenidate. Implications for practice and future research are discussed.